2022
DOI: 10.1038/s42255-022-00677-8
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacological targeting of glutamatergic neurons within the brainstem for weight reduction

Abstract: Food intake and body weight are tightly regulated by neurons within specific brain regions, including the brainstem, where acute activation of dorsal raphe nucleus (DRN) glutamatergic neurons expressing the glutamate transporter Vglut3 (DRNVglut3) drive a robust suppression of food intake and enhance locomotion. Activating Vglut3 neurons in DRN suppresses food intake and increases locomotion, suggesting that modulating the activity of these neurons might alter body weight. Here, we show that DRNVglut3 neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 74 publications
2
7
0
Order By: Relevance
“…Consistently, using fluorescent 5HT sensor we found that extracellular 5HT levels parallel the increased DRN SERT axonal activity. These findings are in line with earlier dialysis studies showing increased 5HT levels in LH in response to food and CCK and that DRN projections to LH is anorexigenic [ 20 , [27] , [28] , [29] ] and provides evidence that increased serotonergic activity extends to BNST as well. Together with axonal imaging, our results suggest that DRN is a key brain region supplying nutrient-related serotonergic input to these regions to suppress food intake.…”
Section: Discussionsupporting
confidence: 92%
“…Consistently, using fluorescent 5HT sensor we found that extracellular 5HT levels parallel the increased DRN SERT axonal activity. These findings are in line with earlier dialysis studies showing increased 5HT levels in LH in response to food and CCK and that DRN projections to LH is anorexigenic [ 20 , [27] , [28] , [29] ] and provides evidence that increased serotonergic activity extends to BNST as well. Together with axonal imaging, our results suggest that DRN is a key brain region supplying nutrient-related serotonergic input to these regions to suppress food intake.…”
Section: Discussionsupporting
confidence: 92%
“…The rough distribution of orexin receptors was reported in rat brains by radiolabeled probes approximately 20 years ago and is still the most comprehensive information available (23,24). Cell resolution information of OX1R and OX2R has been available only for brain regions that abundantly express orexin receptors, such as the amygdala, tuberomammillary nucleus, raphe nuclei, locus coeruleus, and laterodorsal tegmental nucleus (14,(25)(26)(27)(28). At this time, the Allen Brain Atlas fails to show positive signals for orexin receptors and reliable antibodies for OX1R and OX2R that work for immunohistochemistry are not available.…”
Section: Introductionmentioning
confidence: 99%
“…These findings add an important new component to the neural circuit that regulates appetite and adiposity, while also shedding new light on the mechanisms by which leptin regulates this system. Finally, pharmacologic activation of these neurons could have therapeutic implications to reduce weight or to suppress the negative valence associated with hunger 66 .…”
Section: Discussionmentioning
confidence: 99%